Implementation strategy for teaching the pharmacists' patient care process to first year student pharmacists. Issue 10 (12th August 2021) - Bacci, Jennifer L.; Odegard, Peggy; Jefferson, Curtis G.; Blanchard, Carrie M.
Abstract: Objectives: This study aimed to (1) name, define, and operationalize an implementation strategy utilized to teach the Pharmacists' Patient Care Process (PPCP) within a first‐year pharmacy practice course series and (2) evaluate the strategy's impact on students' self‐reported competence in providing the PPCP and subjective, objective, assessment, and plan (SOAP) note performance. Methods: The implementation strategy was described using the Expert Recommendations for Implementation Change (ERIC) terminology and the reporting recommendations developed by Proctor and colleagues. The implementation strategy consisted of developing educational material and conducting training via 7 in‐class workshops and auditing and providing feedback via a 6‐part longitudinal assignment. The validated Comprehensive Medication Management Patient Care Process Fidelity Assessment (CMM PCPFA) was adapted to the educational context and administered to students in March 2020 after completion of the course series to retrospectively assess their self‐perceived change in competence in providing the PPCP. Items were aggregated at the essential function (EF) level. Mean retrospective pre and post EF scores were compared using paired sample t ‐tests. Students' performance on SOAP note submissions were analyzed using descriptive statistics. Results: One hundred seven students (98%) completed the adapted CMM PCPFA and were included in this analysis. The paired t tests showed a statistically significant change in students' self‐reported competence for each essential function. The mean individual student score on their SOAP note was 87.6% ± 11%. Conclusions: Findings suggest the implementation strategy was successful in increasing students' perceived competence in providing the PPCP. Employing an effective implementation strategy across pharmacy curricula is key to developing competent pharmacists and consistency in patient care delivery in practice.